2020
DOI: 10.3390/ijerph17031011
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances Rate among Medical and Allied Health Professions Students in Iran: Implications from a Systematic Review and Meta-Analysis of the Literature

Abstract: Medicine and healthcare professions are prestigious and valued careers and, at the same time, demanding, challenging, and arduous jobs. Medical and allied health professions students, experiencing a stressful academic and clinical workload, may suffer from sleep disturbances. In Iran, several studies have been conducted to explore the prevalence rate among medical and healthcare professions students. The aim of this systematic review and meta-analysis was to quantitatively and rigorously summarize the existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…In the present study, 30.9% participants reported sleep deprivation and the reason for inadequate sleep were the use of mobile phone, media, and friends among 71.4% participants and for 42% participants reported that it was due to study and stress. These results are in line with other studies[ 16 22 23 ], which reported the use of mobile and stress were the major factors for disturbed sleep pattern among budding health care professionals. Study shows that disturb sleep pattern may result in depression, anxiety, improper interpersonal relationship, poor academic performance, and more vulnerability to substance abuse.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 30.9% participants reported sleep deprivation and the reason for inadequate sleep were the use of mobile phone, media, and friends among 71.4% participants and for 42% participants reported that it was due to study and stress. These results are in line with other studies[ 16 22 23 ], which reported the use of mobile and stress were the major factors for disturbed sleep pattern among budding health care professionals. Study shows that disturb sleep pattern may result in depression, anxiety, improper interpersonal relationship, poor academic performance, and more vulnerability to substance abuse.…”
Section: Discussionsupporting
confidence: 93%
“…The symptoms associated with stress are usually accompanied by adjustment, anxiety, and behavioral, sleeping, and emotional disorders [ 10 ]. In addition, a lack of sleep affects memory and decreases alertness, and if it becomes chronic it can lead to disorders such as anxiety and depression, and even vascular comorbidity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, findings vary among countries. In Pakistan, 77% of medical students had poor quality of sleep and a mean PSQI score (SD) of 8.1 (3.1) [ 25 ], compared to 58% of Iranian medical students [ 26 ]. In Egypt, 53% had poor quality of sleep and a mean PSQI score (SD) of 6 (2.7) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%